Non-equilibrium band broadening, gap renormalization and band inversion in black phosphorus. (28th January 2021) - Hedayat, H; Ceraso, A; Soavi, G; Akhavan, S; Cadore, A; Dallera, C; Cerullo, G; Ferrari, A C; Carpene, E
Abstract: Black phosphorous (BP) is a layered semiconductor with high carrier mobility, anisotropic optical response and wide bandgap tunability. In view of its application in optoelectronic devices, understanding transient photo-induced effects is crucial. Here, we investigate by time- and angle-resolved photoemission spectroscopy BP in its pristine state and in the presence of Stark splitting, chemically induced by Cs ad-sorption. We show that photo-injected carriers trigger bandgap renormalization, and a concurrent valence band flattening caused by Pauli blocking. In biased samples, photo-excitation leads to a long-lived (ns) surface photovoltage of few hundreds mV that counterbalances the Cs-induced surface band bending. This allows us to disentangle bulk from surface electronic states, and to clarify the mechanism underlying the band inversion observed in bulk samples.